Rationalisation of idigenous technical knowledge on production management in the farm production systems of Palakkad district - Rajesh P (Department of Agricultural Extension, College of Horticulture, 2003)
Indigenous Technical Knowledge (ITK) was recognized as a possible key to low external input sustainable agriculture that contributes both to sustainable agricultural production for the farmers, as well as a source of knowledge that can add on to the existing science based knowledge of the researchers. Identifying, documenting and incorporating indigenous knowledge systems into agricultural extension organizations were essential to achieve sustainable agricultural development. Keeping in VIew the objectives of the study and the perusal of available literature shows that most of the attributes included in the study were expost facto in nature and in expost facto studies the chance for manipulation by the researcher is very less. The study was conducted in Palakkad district. A multi stage sampling procedure was followed for selection of samples for the study. Out of the 13 developmental blocks five were selected based on the criteria of highest agricultural predominance and presence of at least three production systems out of five envisaged in the study namely rice based, homestead based mixed farming system, plantation including spices, seasonal crops and annual crops. One of the blocks was selected to represent one agro eco zone. Four panchayats were selected within each block based on the same criteria of highest agricultural predominance and presence of at least three production systems out of five. Thus 20 panchayats were included for the study. The objectives of the study necessitated the involvement of three types of respondents viz.,farmers, extension personnel and scientists. These three groups were referred as Farmers Sub System (FSS), Extension Sub System (ESS) and Research Sub System (RSS) respectively.